Uso de los software matemáticos en la carreras de matemáticas e ingeniería: Una Revisión de la Literatura - Navarro Honda, Pol Ever (2025)
The use of mathematical software has become a key tool for supporting teaching and learning in university-level Mathematics and Engineering programs. This study aimed to analyze, through a systematic literature review, recent trends in its educational application during the 2020–2024 period. The document search was conducted in recognized academic databases, applying strict inclusion criteria, resulting in the selection of 39 scientific articles. The analysis identified four thematic categories: software use in algebraic processes, virtual learning environments, statistical and numerical analysis, and pedagogical impact in higher education. Tools such as GeoGebra, Matlab, EViews, and RStudio were frequently mentioned, with reported improvements in conceptual understanding, content visualization, academic performance, and student motivation. The findings reveal that mathematical software goes beyond a technical function, becoming a pedagogical strategy with high potential for educational innovation. The study concludes that its effective integration requires curriculum planning, teacher training, and institutional policies that support its contextualized implementation.